Measuring Health-Related Quality of Life in Tuberous Sclerosis Complex - Psychometric Evaluation of Three Instruments in Individuals With Refractory Epilepsy - Petrus J. de Vries; David N. Franz; Paolo Curatolo; Rima Nabbout; Maureen Neary; Fabian Herbst; Kate Sully; Elaine Brohan; Bryan Bennett; John A. Lawson (Frontiers Media S.A., 2018)
Tuberous sclerosis complex (TSC) is a rare genetic disease associated with significant disease burden and considerable impact on health-related quality of life (HRQL). Currently no disease-specific clinical outcome assessments evaluate HRQL in individuals with TSC. A multi-center phase III study EXIST-3 (NCT01713946) assessed the efficacy and safety of two trough exposure ranges (Low exposure, LE: 3-7 ng/mL and high exposure, HE: 9-15 ng/mL) of adjunctive everolimus in patients aged 2-65 years with TSC and refractory partial-onset seizures (N = 366). Three age-specific HRQL measures were included as secondary endpoints including: quality of life in childhood epilepsy (QOLCE; caregiver-report for aged 2- < 11), the Quality of Life in Epilepsy Inventory for Adolescents-48 (QOLIE-AD-48; self-report, aged ≥ 11- < 18), and the Quality of Life in Epilepsy Inventory-31-Problems (QOLIE-31-P; self-report, aged ≥ 18). Intellectual ability was evaluated using the Wechsler Non-Verbal (WNV) Scale of Ability. Post hoc analyses were performed on the core phase primary data from EXIST-3 to evaluate the psychometric properties of the HRQL measures and calculate meaningful change estimates. Results showed that a significant subset of the trial sample (4-21 year olds) scored in the intellectual disability range, as assessed by the WNV. Psychometric analyses of the three epilepsy measures (including reliability, validity, and ability to detect change) supported the appropriateness for use in TSC. Distribution-based meaningful change estimates were generated for each HRQL measure, with estimates for the QOLIE-31-P total score largely consistent with the published literature. To our knowledge, this is the first evaluation using clinical trial data to establish the psychometric properties of the QOLCE, QOLIE-AD-48, and QOLIE-31-P for use in individuals with TSC. These findings increase confidence in the measures as valid and reliable for use in clinical trials and future research in patients with TSC.